First-Pass Reperfusion by Mechanical Thrombectomy in Acute M1 Occlusion: The Size of Retriever Matters - Serna Candel, Carmen; Aguilar Pérez, Marta; Bäzner, Hansjörg; Henkes, Hans; Hellstern, Victoria (Frontiers in Neurology, 2021)
Introduction: Achieving sufficient or complete reperfusion in only one pass of thrombectomy should be pursued in endovascular treatment of acute large vessel occlusions (LVO). Thrombectomy with stent retriever is considered one of the standard techniques nowadays. The optimal size of stent retrievers for thrombectomy, however, is not yet established. Methods: Aim of this study was to evaluate the results of aspiration-assisted mechanical thrombectomy of acute isolated occlusion of the middle cerebral artery (MCA) in the M1 segment with a novel 5x40 mm stent retriever compared to the usual 4x20 mm device. The achieved recanalization was measured by the “Thrombolysis In Cerebral Infarction” score (TICI). We hypothesized that thrombectomy of M1 occlusions with 5x40 stent retrievers yields higher rates of first pass effect (FPE) (TICI≥2c after one pass) and modified FPE (mFPE) (TICI≥2b after one pass) than thrombectomy with 4x20. We included isolated M1 occlusions treated with pRESET 5x40 (phenox) as first choice device for thrombectomy and compared with M1 occlusions treated with pRESET 4x20. We excluded patients with additional occlusions, tandem stenosis or that received an intracranial stent or angioplasty as a part of the endovascular treatment. Results: The 5x40 group achieved higher FPE compared to the 4x20 group (61.4%, 35 of 57 patients versus 40.7%, 46 of 113 respectively; adjusted odds ratio and 95% confidence interval (OR (95%CI) 2.20(1.08-4.48), p=0.030); and a higher mFPE (68.4%, 39 of 57 patients vs 48.7%, 55 of 113; adjusted OR 2.11(1.04-4.28), p=0.037). Frequency of sufficient reperfusion (TICI≥2b) was similar in both groups (100% versus 97.3%) but frequency of successful reperfusion (TICI≥2c) was higher in the 5x40 group (82.5% versus 61.9%, adjusted OR 2.47(1.01-6.04), p=0.047). Number of passes to achieve reperfusion was significantly lower in the 5x40 group than in 4x20 group (1.6±1.1 vs 2±1.4, p=0.033; adjusted incidence rate ratio (IRR) 0.84(0.69-1.03) p=0.096). mRS at 90 days was similar in both groups. Conclusions: The size of stent retriever matters in acute M1 occlusions treated with aspiration-assisted mechanical thrombectomy. A longer stent retriever with a larger nominal diameter achieves a higher FPE and mFPE and higher successful reperfusion compared to a shorter stent retriever.